STRATEGI REBRANDING DAN TRANSFORMASI KEMASAN RAMAH LINGKUNGAN PADA PRODUK "CEMIGO" BROWNIES BITE UNTUK MENINGKATKAN DAYA SAING DI PASAR MILENIAL - Adinda Ratu Puri; Cut Rafa Auliya Qolby; Elisabeth Helsa Kurnia; Nurul Pitriyani; Purwani Setyaningrum (Journal Inclusive Society Community Servies, 2026)
This community service aims to increase the competitiveness of the culinary UMKM "Cemigo" through brand identity renewal, replacing plastic packaging with environmentally friendly paper bowls, and designing a youth-targeted marketing strategy with participatory methods in the form of brand evaluation, packaging redesign, and market testing on 50 respondents. The data collection techniques used were structured questionnaires, deep interviews, and organoleptic testing to measure consumer acceptance. The results showed a significant increase in consumer quality perception by 45%, visual attraction by 92%, and consumer interest in eco-friendly aspects by 82%. Furthermore, the technical test proved that paper bowl packaging preserves the crunchy yet moist texture of the brownies 20% longer compared to the previous plastic mika. This intervention effectively strengthens product positioning and boosts sales in the millennial segment while supporting green economy practices.